Penerapan Teknik Napas Dalam Untuk Menurunkan Kejadian Mual Muntah Pasca Spinal Anestesi - Andang Sudarmono; Tri Budi (Lembaga Pengembangan Kinerja Dosen, 2021)
Post-spinal anesthesia nausea and vomiting (PSANV) are common side effects that can affect patient comfort and recovery after surgery. This condition often disrupts the recovery process and may extend the post-operative care period. One non-pharmacological method that can help reduce nausea and vomiting is deep breathing techniques. This study aims to evaluate the effectiveness of deep breathing techniques in reducing the incidence of nausea and vomiting after spinal anesthesia. The method used in this study is a pre-test and post-test design, with an intervention consisting of deep breathing exercises for patients undergoing surgery with spinal anesthesia. A pre-test was conducted before the intervention to assess the incidence of nausea and vomiting in patients. After patients practiced deep breathing exercises for a certain period, a post-test was performed to evaluate changes in the frequency of nausea and vomiting post-operation. The results showed a significant reduction in the frequency of nausea and vomiting after patients practiced deep breathing techniques. This technique has proven to be a simple, safe, and effective method to enhance post-operative comfort. Therefore, the implementation of deep breathing techniques can be recommended as part of post-spinal anesthesia management in healthcare facilities to improve patient recovery quality.